PENGARUH INTENSITAS MODAL, LEVERAGE, DAN KEPEMILIKAN ASING TERHADAP KEPUTUSAN PERUSAHAAN MELAKUKAN TRANSFER PRICING - Dewi, Sartika; Illahi, Ilham (STIE Perbankan Indonesia, 2024)
The aim of this research is to find out how factors including capital intensity, leverage, and foreign ownership affected the decision to implement transfer pricing by the company. For the years 2018–2022, the data came from the financial reports of the Kompas100 index businesses traded on the Indonesia Stock Exchange. This data is considered secondary. This study employs an associative quantitative approach. With the use of purposive sampling, 66 out of 100 companies were able to be included in the final sample for this study. Methods for analyzing data and assessing hypotheses often make use of tests for multiple linear regression, hypothesis testing, classical assumptions, and descriptive statistics. So that SPSS 25.0 software can be used to examine the data. This study found that transfer pricing is positively affected by capital intensity, positively affected by foreign ownership, and positively affected by leverage. From 2018 to 2022, transfer pricing in the kompas100 index companies listed on the Indonesia Stock Exchange was impacted by capital intensity, leverage, and foreign ownership all at once. Keywords: Transfer Pricing, Capital Intensity, Leverage, Foreign Ownership